COMPLICATIONS IN THE MAXILLOFACIAL REGION IN PATIENTS WHO HAVE SUFFERED FROM COVID-19 (Journal of Science-Innovative Research in Uzbekistan, 2024)
This article is a review of clinical cases describing complications in the maxillofacial area in patients who have recovered from COVID-19. The study includes analysis of a variety of manifestations of infection beyond respiratory symptoms and focuses on the impact of the virus on the condition of the facial anatomy and maxillofacial system. Various aspects are considered, such as the influence of cytokines, receptors and inflammatory processes on the tissues of the facial area. The result is a comprehensive overview of the variation in complications, including effects on the salivary glands, neurotropic effects, and those associated with the use of medical therapies. The summary of these cases highlights the importance of paying attention to the maxillofacial region in COVID-19 survivors and calls for additional research to better understand the effects of the virus on this anatomical region